(untitled) (Texas Journal of Medical Science, 2022)
In the present study, experimental models of chronic toxic hepatitis were induced by intragastric, subcutaneous and intraperitoneal administration of a solution of heliotrin. Hematological, biochemical and morphological research methods were used to assess the severity of liver damage. Based on the data obtained, toxic hepatitis was confirmed in three models. The most severe liver lesions occur with intraperitoneal administration of heliotrin. Oral or intragastric administration of heliotrin reduces the mortality rate (from 8% to 10%), avoids violation of the integrity of the skin and reduces the manifestation of pain syndrome in animals.